Kasus Kekerasan Terhadap Perempuan Pada Misi MINUSTAH di Haiti Tahun 2004-2017 - Surya Edi, I Wayan; Kumala Dewi, Putu Ratih; Kawitri Resen, Putu Titah (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2019)
ABSTRACT This study aims to explain how sexual violence in the form of Sexual Exploitation and Abuse occurred in Haiti during the MINUSTAH peace mission through the perspective of liberal feminism that occurred in 2004 to 2017. One of MINUSTAH's mandates related to the protection of civilians, namely the mandate of the PoC. Women in Haiti who have little education and military culture which are usually dominated by men encourage the placement of armed forces in the hands of many men. This indirectly increases men's access to SEA. For Liberal Feminists, women as a group is only protected from all forms of violence done by armed groups but not by peacekeepers. For Liberal Feminists, increasing the number and role of women in peace missions in all fields can reduce the existing hypermasculinity which has also become one of the factors causing SEA. Keywords: Haiti, MINUSTAH, SEA, Liberal Feminism